KINERJA PENYULUHAN DALAM PEMBERDAYAAN PETANI PADI DI KABUPATEN INDRAGIRI HILIR - Fiki Afrialfa; Rosnita Rosnita; Roza Yulida (Indonesian Journal of Agricultural Economics, 2019)
The objectives of the research are: (1) analyze the performance of extension workers from (Competence, Roles, Independence, and Social) (2) analyze the level of empowerment independence of farmer. The research conducted in Indragiri Hilir regency Kempas, Batang Tuaka and Keritang district. Samples taken with population and purposive sampling, with 156 independent smallholder sample from farmer group and  42  sample from agricultural extension. Data analysis used likert scale. Conclusion (1) The performance of extension worker who has been running in the field of rice farming business in Indragiri Hilir regency has been running "Good". Already carrying out the task of counseling with its own ability, the indicators that affect the performance as a role (2) Level empowerment of rice farmers in Indragiri Hilir regency after the overall performance of agricultural extension in the category "Power" has been running well, indicators that affecting human resources. The independence of rice farmers in Indragiri Hilir Regency has good overall extension performance in the "Independence" category. Indicators that greatly affect Social Self-reliance.